Cissus notabilis, a new name for extant Cissus spectabilis (Vitaceae) - Doweld, Alexander Borisovitch (Phytotaxa, 2015)
The creation of the International Fossil Plant Names Index (IFPNI, 2014 onwards) with the aim of listing of all fossil plant species reveals a few new cases of homonymy between fossil and extant species. The name Cissus spectabilis (Kurz) Planchon (1887: 1092), originally published as Vitis spectabilis Kurz (1874: 196), is an illegitimate later homonym of Cissus spectabilis Heer (1878: 45) (Art. 53.1 of the ICN, McNeill et al., 2012). C. spectabilis Heer is a fossil-species currently accepted (Kirchheimer 1939, Sosnowsky 1949, 1974, Kryshtofovich & Baikovskaja 1960), described from the Upper Cretaceous (Coniacian) deposits of Sakhalin island (Far East, Russian Federation). Since the preoccupied extant species C. spectabilis (Kurz) Planch., a narrow Indian endemic restricted to Sikkim, Siliguri and neighboring localities of West Bengal, is also currently recognized as a valid species (The Plant List 2013 onwards; eFlora of India 2014 onwards) and it does not have any synonym, a nomen novum, C. notabilis, is here formally proposed as a replacement name.